2021
DOI: 10.1002/humu.24164
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of ABCC8 variants of unknown significance based on bioinformatics predictions, splicing assays, and protein analyses: Benefits for the accurate diagnosis of congenital hyperinsulinism

Abstract: ABCC8 encodes the SUR1 subunit of the β‐cell ATP‐sensitive potassium channel whose loss of function causes congenital hyperinsulinism (CHI). Molecular diagnosis is critical for optimal management of CHI patients. Unfortunately, assessing the impact of ABCC8 variants on RNA splicing remains very challenging as this gene is poorly expressed in leukocytes. Here, we performed bioinformatics analysis and cell‐based minigene assays to assess the impact on splicing of 13 ABCC8 variants identified in 20 CHI patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…RNA analysis using either patient blood cells or immortalized lymphoblastoid cells represents an alternative option, providing that the gene of interest is normally expressed in these cells (Wai et al, 2020). In case of the non-feasibility of both approaches, a cell culture-based minigene splicing assay has often been devised (for some most recent examples, see Damasio et al, 2021;Hao et al, 2021;Kim et al, 2021;Kortum et al, 2021;Le Tertre et al, 2021;Morbidoni et al, 2021;Qian et al, 2021;Saint-Martin et al, 2021;Torrado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…RNA analysis using either patient blood cells or immortalized lymphoblastoid cells represents an alternative option, providing that the gene of interest is normally expressed in these cells (Wai et al, 2020). In case of the non-feasibility of both approaches, a cell culture-based minigene splicing assay has often been devised (for some most recent examples, see Damasio et al, 2021;Hao et al, 2021;Kim et al, 2021;Kortum et al, 2021;Le Tertre et al, 2021;Morbidoni et al, 2021;Qian et al, 2021;Saint-Martin et al, 2021;Torrado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This variant has been reported in a heterozygous state in two patients diagnosed with CHI (Park et al, 2016;Saint-Martin et al, 2021) gest birth stress, however, perinatal stress induced hyperinsulinism is a potential nongenetic etiology, as it leads to diazoxide-responsive disease that often resolves within the first year of life, a disease course similar to the reported patient (Hoe et al, 2006). The patient reported by Saint-Martin et al, did not respond to diazoxide and was confirmed to have focal disease based on histology.…”
Section: Discussionmentioning
confidence: 73%
“…We present this case of a patient with severe diffuse CHI and a homozygous c.4608G>A variant in ABCC8 . This variant has been reported in a heterozygous state in two patients diagnosed with CHI (Park et al, 2016; Saint‐Martin et al, 2021). A Korean patient reported by Park et al responded well to treatment with diazoxide and octreotide, and after 3 months, the patient had conjectured spontaneous remission.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations